Evaluasi Waktu Tunggu Pelayanan Resep Di Salah Satu Rumah Sakit X Kabupaten Kuningan - Guntur Tedi Koswara; Angga Anugra Diputra (STIKes Muhammadiyah Kuningan, 2018)
One of the Hospital service standards is the waiting time. The public satisfaction of a perceived installation of the hospital's quick pharmaceutical services in providing both concoction and non-concoction. Based on the above description, the authors are interested to know how much waiting time the patient to get non-concoction drugs and concoction from the start reception of the recipe to the delivery of the drug to the patient regarding one of the hospital service standards by examining the prescription service waiting time in one of the X Hospital district Kuningan. This research uses descriptive method that describes something or activity or situation or event in accordance with actual events. The data used is the primary data, the authors will review and observe and record directly waiting time prescription service in one hospital x district Kuningan. The number of samples taken is 50 prescriptions and 50 for non-concocted recipes from 25 May 2017 to 31 May 2017. Based on the conclusions of 50 prescription recipes, the corresponding recipes of 50 recipes and inappropriate recipes.While for the recipe non-concoction of the appropriate recipe of 41 recipes and the incompatibilities of the 9 recipes.